Petrological and Geochemical Evolution of the Kohistan Arc-Batholith, Gilgit, N. Pakistan - Petterson, Michael G.; Windley, Brian F. (Journal of Himalayan Earth Sciences, 1986)
The Kohistan batholith is the most north-westerly part of the Trans-Himalayan batholith which extends some 2700 kms from near Lhasa in the east to Pakistan in the west. Detailed fieldwork of an area of 2500 km2, centred on the town of Gilgit, has shown that the batholith has evolved in three distinct stages. (1) An early bimodal sequence of high-K gabbroic diorites and high SiO2, low K tonalites, which have been deformed and folded, together with associated meta-volcanic and sedimentary country rocks around a major syncline (the Jaglot Syncline). These early plutonics, which comprise 1/3 of the batholith, have a penetrative, gneissose fabric which is orientated parallel to the major structural trends of the area. These rocks formed in an island arc environment. (2) An undeformed sequence of basic dykes, gabbros, diorites, granodiorites and granites which cut the structures associated with the Jaglot Syncline. These rocks formed in an Andean-type continental margin. (3) Extensive swarms of layered aplite-pegmatite sheets, which formed after the terminal collision between India and Eurasia. Some of these rocks formed by crustal melting. Five rock units have yielded Rb-Sr whole rock isochron ages. These are 102 ± 12 Ma for an early, deformed, tonalite, 54 ± 4 Ma and 40 ± 6 Ma for two second stage granitoids, and 34 ± 14 Ma and 29 ± 8 Ma for two late leucogranitic sheets. Even the least evolved gabbros of stages 1 and 2 are enriched in Rb, K, Ba, Sr, P and LREE relative to Nb, Zr, Ti, Y and HREE. With fractionation LFS/HFS, K/Na and LREE/HREE element ratios increase and the batholith displays a calc-alkaline trend with respect to Mg, Fe, Na and K. The main magmatic trend of the batholith can he explained by the fractionation of amphibole-plagioclase-magnetite ± clinopyroxene in the basic-intermediate rocks and plagioclase-K-feldspar-biotite and magnetite in the acid rocks. Zircon, apatite and sphene were important accessory minerals. Low 87Sr/86Sr initial ratios (0.7039- 0.7052) suggest that the ultimate source for the majority of the plutonics was the upper mantle. However, the stage 1 tonalites and some of the stage 3 leucogranites were formed by partial melting.